Remittance inflows, technological innovations, financial development and ecological footprint: A global analysis using PSQR approach - Maria Mazhar; Muhammad Tariq Majeed; Zubia Hussain (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
The present research aims to investigate the influence of remittance inflows on the ecological footprint (EFP). It also seeks to evaluate the interactive effects of technological innovation and financial development on the ecological footprint covering the panel data for 94 countries from 1980 to 2021. Estimation is performed using the software Stata 15 and applying the pooled ordinary least squares (POLS) and panel simultaneous quantile regression (PSQR) techniques. In a worldwide panel, the findings indicate that both remittance inflows and technological innovations reduce EFP. Remittance inflows, in contrast, might degrade environmental quality by encouraging technical advancements and financial development. In addition, the study's finding confirms the environmental Kuznets curve (EKC) theory in most of the quantiles. The overall findings imply that, while remittance inflows are beneficial to environmental quality, they may also degrade it through technical progress and financial development. Therefore, regulating and redirecting remittances toward environmental sustainability will assist governments in meeting their environmental objectives.
Keywords: 330; remittances; technological innovations; patents; financial development; Environmental Kuznets curve; energy consumption; urban population